2019
DOI: 10.1094/mpmi-01-19-0013-r
|View full text |Cite
|
Sign up to set email alerts
|

Pipecolic Acid Is Induced in Barley upon Infection and Triggers Immune Responses Associated with Elevated Nitric Oxide Accumulation

Abstract: Pipecolic acid (Pip) is an essential component of systemic acquired resistance, priming resistance in Arabidopsis thaliana against (hemi)biotrophic pathogens. Here, we studied the potential role of Pip in bacteria-induced systemic immunity in barley. Exudates of barley leaves infected with the systemic immunity–inducing pathogen Pseudomonas syringae pv. japonica induced immune responses in A. thaliana. The same leaf exudates contained elevated Pip levels compared with those of mock-treated barley leaves. Exoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 61 publications
2
23
0
Order By: Relevance
“…Our metabolite analyses suggest that an endogenous activation of SAR in barley might proceed via NHP signaling. This assumption is compatible with the finding that H. vulgare plants fed with exogenous Pip acquired resistance to X. translucens infection ( Lenk et al , 2019 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our metabolite analyses suggest that an endogenous activation of SAR in barley might proceed via NHP signaling. This assumption is compatible with the finding that H. vulgare plants fed with exogenous Pip acquired resistance to X. translucens infection ( Lenk et al , 2019 ).…”
Section: Discussionsupporting
confidence: 90%
“…Pip functions as the direct metabolic precursor of NHP ( Hartmann et al , 2018 ). Previous studies have reported that inoculation with a pathogen markedly induces the accumulation of Pip in different angiosperm species, including Arabidopsis, tobacco, potato, soybean, rice, and barley (Pálfi and Dézsi, 1968; Návarová et al , 2012 ; Vogel-Adghough et al , 2013 ; Aliferis et al , 2014 ; Abeysekara et al , 2016 ; Ádám et al , 2018 ; Lenk et al , 2019 ). Consistently, the results of the present study show that the levels of Pip increase strongly in leaves of tobacco, soybean, and barley inoculated with compatible Pseudomonas bacteria ( Figs 4 , 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, systemic immunity against Blumeria graminis f.sp. hordei might depend on SA, while Pip triggers systemic resistance in barley against both pathogens (Lenk et al ., 2018, 2019). Pip accumulates in barley petiole exudates after a resistance‐inducing infection, and exogenous Pip application induces NO accumulation and primes ROS production (Lenk et al ., 2019), providing evidence for a possible conservation of the Pip pathway of SAR between monocotyledonous and dicotyledonous plants (Fig.…”
Section: Systemic Acquired Resistance (Sar)mentioning
confidence: 99%
“…For determination of SA-and Pip-related metabolites, frozen-materials were crushed to powder and lyophilized. The extraction and measurement of the compounds was carried out as described before with minor modifications (Wenig et al, 2019). Briefly, 20 mg of freeze-dried material was resuspended in 1.5 ml 70% methanol, vigorously shaken at 4 °C for 1 h and subsequently centrifuged at 18.000 x g for 10 min.…”
Section: Lc-ms Analysesmentioning
confidence: 99%